LEXICAL CHOICE IN KARO NARRATIVES - Gabas Junior, Nilson (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper looks at two verbal descriptions of the Pear film and characterizes them according to the analysis proposed by Downing (1980) for factors influencing lexical choice. The two descriptions, one short and one long, were told by my Karo consultant, Mário Jorge Arara, after the exhibition of the film. Generally, the present article looks at Downing’s assertion that "if the description is to be brief, words of broad referential scope are likely to be chosen (...). If the speaker opts for a more detailed description, more lexemes of narrower referential scope are likely to appear" (1980:90) and sees how this assertion applies to the two narratives. Specifically, it looks at each of the versions of the story and tries to explain the mentions of the referents by either basic or non-basic level categories in terms of cognitive, textual and contextual factors.